Peran Orang Tua dalam Pendidikan Bahasa Arab Peserta Didik Pondok Pesantren Darul Quran wal Hadits (Studi Kasus di Martapura Oku Timur) - Nuansah, Nuansah Ari; Ahyat Habibie; Akhmad Huseini (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
The research aims to discuss the role of parents in Arabic language education for students at the Darul Qur'an wal Hadith Islamic boarding school. The role of parents is a way for students/children to develop their potential in exploring and studying Arabic so that they can understand the Al-Qur'an and Sunnah properly and correctly. The type of research used is descriptive qualitative, carried out by observation, in-depth interviews and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the research show that, 1) The role of attention in protecting, supervising, motivating, providing tools and facilities to improve learning in children, 2) Method of applying Arabic from parents to children at the Darul Qur'an wal Hadith Islamic Boarding School by listening, reading , writing, and also by memorizing the vocabulary around them because the desire to have children who have proficiency in Arabic and who can understand the Al-Qur'an and As-Sunnah correctly is certainly every parent's dream. Investment and the rewards they await in this world and the hereafter are the main drivers for them, 3) The Urgency of Arabic in the Islamic View, Arabic plays a very important role. Especially in deepening the knowledge of the Koran and Hadith. Because in essence parents are the first madrasah for their children and it is not enough just to learning to teach at school.